PENGARUH HARGA, KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN DI UNYIL DURIAN PEKANBARU - Jone's Christentio Rikin; Fathorrahman; Theresia Pradiani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
In the business world, competition to win customers' hearts is inevitable. The increasingly intense business competition compels business actors, particularly in the durian industry, such as Unyil Durian Pekanbaru, to optimize their performance. One of the challenges is to create buying decisions for Unyil Durian Pekanbaru's products so that customers remain loyal and continue to make repeat purchases. This study aims to identify and analyze the influence of price, product quality, and service quality on purchasing decisions at Unyil Durian Pekanbaru. This research adopts a quantitative method. The sampling technique used is non-probability sampling with a purposive sampling method, targeting individuals who have previously purchased Unyil Durian Pekanbaru's products. The sample consists of 100 respondents residing in Pekanbaru City, and data collection is conducted using questionnaires. Data analysis involves classical assumption testing, multiple linear regression analysis, and hypothesis testing, including the determination coefficient test, t-test, and F-test. The results of the study reveal the following findings: (1) Price has a significant influence and negative on purchasing decisions, (2) Product quality has a significant influence on purchasing decisions, (3) Service quality has a significant influence on purchasing decisions. Simultaneously, the study concludes that price, product quality, and service quality collectively influence buying decisions.